Investigation of oral and fecal colonization with candida species and associated factors in human immunodeficiency virus-infected children in Turkey - KEPENEKLİ KADAYİFCİ, EDA (My University, 2023)
Objective The risk of endogenous infections in human immunodeficiency virus (HIV)-infected individuals increases with Candida species colonized in mouth and intestinal areas. The predisposing factors for colonization and the prevalence of different Candida spp. in HIV-infected Turkish children remain unknown. This study aimed to determine the colonization frequency and risk factors of colonization with Candida species in oral and fecal samples of HIV-infected pediatric patients in relation to a control group.Methods Oral and feces samples of 22 HIV-infected and 52 healthy children were plated onto CHROMagar and CHROM-Pal-agar. Yeasts were identified by conventional methods, and strains with insufficient identification were identified by molecular techniques.Results Candida spp. were detected in oral/fecal samples of 50%/68.2% HIV-infected and 36.5%/73.1% healthy children. The most common species was Candida albicans in oral and fecal samples of HIV-infected (31.8 and 31.8%) and healthy (26.9 and 48.1%) children. The most frequently non-albicans species in oral samples was Candida dubliniensis (18.2%) in HIV-infected children and Candida parapsilosis (3.8%) in healthy children. In feces samples, C. parapsilosis , Candida glabrata , and Candida krusei were most frequent (13.6%, each) in HIV-infected patients, and Candida kefyr (11.5%) was most frequent in controls. There was a significant association between oral C. dubliniensis colonization and HIV infection ( p = 0.006). Yeast carriage was not associated with gender and viral load in HIV-infected patients.Conclusion The isolation of C. dubliniensis from oral and fecal samples of pediatric HIV patients was done for the first time in Turkey in the present study. Additional studies are needed to clarify the factors associated with oral and fecal Candida colonization in these children.
Keywords: Tıp; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Medicine; Internal Medicine Sciences; Child Health and Diseases; Life Sciences; Health Sciences; Natural Sciences; BULAŞICI HASTALIKLAR; İmmünoloji; Yaşam Bilimleri (LIFE); PEDİATRİ; Klinik Tıp; Klinik Tıp (MED); INFECTIOUS DISEASES; IMMUNOLOGY; Life Sciences (LIFE); PEDIATRICS; CLINICAL MEDICINE; Clinical Medicine (MED); Pediatri; Pediatri, Perinatoloji ve Çocuk Sağlığı; Bulaşıcı hastalıklar; Genel İmmünoloji ve Mikrobiyoloji; Pediatrics; Pediatrics, Perinatology and Child Health; Infectious Diseases; Immunology; General Immunology and Microbiology; HIV; children; Candida; oral colonization; fecal colonization; ACTIVE ANTIRETROVIRAL THERAPY; RIO-DE-JANEIRO; HEALTHY-CHILDREN; IMMUNOGLOBULIN-A; HIV PATIENTS; CARRIAGE; YEAST; RINSE; MANIFESTATIONS; DUBLINIENSIS; HIV; children; Candida; oral colonization; fecal colonization